Digital Competence for Pedagogical Integration: A Study with Elementary School Teachers in the Azores - Ana Claudia Loureiro; Ana Isabel Santos; Manuel Meirinhos (Education Sciences)
This study builds on previous research carried out in 2021 on the self-perception of elementary school teachers in Portugal regarding their digital competences for the pedagogical integration of technologies in educational contexts. In order to verify this perception throughout the country, we extended the research to include teachers from the Autonomous Region of the Azores (ARA), considering the following objectives: (i) to verify teachers’ digital competences; (ii) to identify their levels of digital competence; and (iii) to identify the level of influence of training on the categorization of teachers’ level of digital competence. This is an exploratory study that used an online questionnaire based on the digital competences in Area 2 of the DigCompEdu framework. Two hundred seven teachers took part in this study. The results revealed that teachers seem to feel capable of using technology but need to improve their ability to adapt digital resources for student learning. The global mapping of digital competences will make it possible to verify these competences, these attitudes and abilities, and the integration of ICT into teaching practices as well as helping to outline future projects and guidelines in the area of teacher training in the ARA in particular.